Regulatory influence on market conditions in the banking union: The cases of macro-prudential instruments and the bail-in tool - Tobias H. Tröger (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
This paper looks into the specific influence that the European banking union will have on (future) bank client relationships. It shows that the intended regulatory influence on market conditions in principle serves as a powerful governance tool to achieve financial stability objectives. From this vantage, it analyzes macro-prudential instruments with a particular view to mortgage lending markets - the latter have been critical in the emergence of many modern financial crises. In gauging the impact of the new European supervisory framework, it finds that the ECB will lack influence on key macro-prudential tools to push through more rigid supervisory policies vis-à-vis forbearing national authorities. Furthermore, this paper points out that the current design of the European bail-in tool supplies resolution authorities with undue discretion. This feature which also afflicts the SRM imperils the key policy objective to re-instill market discipline on banks' debt financing operations. The latter is also called into question because the nested regulatory technique that aims at preventing bail-outs unintendedly opens additional maneuvering space for political decision makers.
Keywords: E44; G01; G18; G21; G28; K22; K23; 330; banking union; macro-prudential supervision; real estate lending; bail-in; market discipline